2013
DOI: 10.1007/s11695-013-1016-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bariatric Surgery on Bone Mineral Density: Comparison of Gastric Bypass and Sleeve Gastrectomy

Abstract: The aim of our study was to compare bone mineral density (BMD) a year after Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (SG) in age- and body mass index-matched women. In 33 morbidly obese women undergoing RYGB and 33 undergoing SG, plasma determinations of calcium, parathyroid hormone (PTH), 25-hydroxyvitamin D (25(OH) D3), and insulin-like growth factor-I (IGF-I) were made prior to and at 12 months after surgery. Dual-energy X-ray absorptiometry was performed in all patients 1 year after surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 33 publications
2
75
1
1
Order By: Relevance
“…Similarly, the weighted mean 25(OH)D levels of studies divided into 2 categories (mean BMI ≥ 50 kg/m 2 versus mean BMI <50 kg/m 2 ) also did not differ significantly (data not shown). Two other studies [78,79], in addition to the restrictive procedure arm of a third one [69] were not represented on Figure 2, as the number of participants per surgical procedure group was < 50. These studies also showed a mean 25(OH)D level of less than 20 ng/ml before bariatric surgery (Appendix).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the weighted mean 25(OH)D levels of studies divided into 2 categories (mean BMI ≥ 50 kg/m 2 versus mean BMI <50 kg/m 2 ) also did not differ significantly (data not shown). Two other studies [78,79], in addition to the restrictive procedure arm of a third one [69] were not represented on Figure 2, as the number of participants per surgical procedure group was < 50. These studies also showed a mean 25(OH)D level of less than 20 ng/ml before bariatric surgery (Appendix).…”
Section: Resultsmentioning
confidence: 99%
“…72 . The one study that found similar bone loss at the spine and hip after SG and RYGB also had similar excess weight loss and calciotropic hormone levels eliminating the differences in those factors that might be expected to affect bone density 73 .…”
Section: Skeletal Consequences Of Bariatric Surgerymentioning
confidence: 97%
“…Fewer data are available for the relatively newer sleeve gastrectomy. A longitudinal study shows that laparoscopic sleeve gastrectomy (LSG) may lead to a significant decline in BMD at the spine and proximal femur [71] and in a study comparing the effects of RYGB and SG on age-and BMI-matched morbidly obese women, BMD at the femoral neck and the lumbar spine 1 year after bariatric surgery was similar between the two groups [108], suggesting that even if SG is not a typical malabsorptive procedure, it might have effects that are similar to RYGB. In contrast, in another 2-year follow-up study of patients undergoing LSG, a significant increase in BMD of the lumbar spine was demonstrated mainly during the first year post-surgery [109].…”
Section: Effects Of Bariatric Surgery On Bmdmentioning
confidence: 99%